Metastatic breast cancer: clinicopathological features and survival according to the site of metastasis - Brum, Igor Vilela; Guerra, Maximiliano Ribeiro; Cintra, Jane Rocha Duarte; Bustamante-Teixeira, Maria Teresa (Medicina (Ribeirao Preto), 2017)
Study design: retrospective cohort study. Objectives: investigate clinical and pathological features, as well as the survival of metastatic breast cancer according to the site affected by the metastasis, osseous or extraosseous. Methods: the study population consisted of a cohort of 124 women with metastatic breast cancer assisted in an oncology referral hospital. The association between sociodemographic, tumoral and treatment variables and the site of metastasis was assessed with a chi-square test and the survival functions were estimated by the Kaplan-Meier method. Results: osseous-only metastasis was observed in 26.6% of patients and extra-osseous metastasis in 45.2%, the remainder presented metastasis in both sites. Among patients with osseous-only metastasis, 68.2% had been treated with hormonal therapy, compared with 44.9% of those with extraosseous metastasis (p=0.06); progesterone receptor–positive tumors were found in 63.6% and 43.3% of the patients in each group (osseous-only versus extraosseous), respectively (p=0.09). Overall 5-years survival rate was 38.5% (CI95%: 18.6-58.2) for patients with osseous-only metastasis and 24.8% (CI95%: 15.2-35.7) for patients with extraosseous metastasis. The mean survival time after the diagnosis of metastasis was 19.6 months in cases of bone-only metastasis and 12.1 in extraosseous metastasis. Conclusions: hormone receptor positivity and use of hormone therapy seem to be associated with the occurrence of isolated bone metastasis; patients within this group were suggested to have longer survival times.